2006
DOI: 10.1111/j.1440-1681.2006.04420.x
|View full text |Cite
|
Sign up to set email alerts
|

UPREGULATION OF ANGIOTENSIN AT1 RECEPTOR AND INTRACELLULAR KINASE GENE EXPRESSION IN HYPERTENSIVE RATS

Abstract: 1. Activation of angiotensin II AT1 receptors (AT1R) stimulates catecholamine systems within both central and peripheral tissues that are associated with blood pressure control. In the present study, we sought to determine whether the hypertensive phenotype of the spontaneously hypertensive rat (SHR) is associated with changes in AT1R gene expression and whether gene expression of downstream signalling molecules was coupled to catecholamine gene expression, both in key brainstem nuclei and in peripheral sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 28 publications
5
60
0
3
Order By: Relevance
“…6 AT 1 R is rich in the specific brain nuclei that regulate SNS activation, such as the anteroventral third ventricle, paraventricular nucleus of the hypothalamus, nucleus tractus solitarii and RVLM. [48][49][50] Moreover, a high density of AT 1 R is present in the brain regions involved in the regulation of SNS activation, such as the circumventricular organs outside of the bloodbrain barrier, where peripherally administered ARBs are able to effect change without consideration of the blood-brain barrier, as well as inside of the blood-brain barrier. 50 The reduction of oxidative stress via inhibition of AT 1 R caused by orally administered TLM may not be a phenomenon unique to the RVLM.…”
Section: Discussionmentioning
confidence: 99%
“…6 AT 1 R is rich in the specific brain nuclei that regulate SNS activation, such as the anteroventral third ventricle, paraventricular nucleus of the hypothalamus, nucleus tractus solitarii and RVLM. [48][49][50] Moreover, a high density of AT 1 R is present in the brain regions involved in the regulation of SNS activation, such as the circumventricular organs outside of the bloodbrain barrier, where peripherally administered ARBs are able to effect change without consideration of the blood-brain barrier, as well as inside of the blood-brain barrier. 50 The reduction of oxidative stress via inhibition of AT 1 R caused by orally administered TLM may not be a phenomenon unique to the RVLM.…”
Section: Discussionmentioning
confidence: 99%
“…22,24,42 It is interesting to note that AT1 receptors are rich in the specific brain nuclei that regulate the sympathetic activity such as the anteroventral third ventricle, paraventricular nucleus of the hypothalamus, NTS and the RVLM in the brainstem. 46,47,76 It has been demonstrated that the peripheral administration of the AT1 receptor blockers penetrate the blood-brain barrier and blocks the AT1 receptors within the brain as well as outside of the brain, although the extent of the blocking action within the brain varies among the AT1 receptor blockers when they are administered peripherally. 77 There are two important observations in this regard.…”
Section: Effects Of At1 Receptor Blockers On Oxidative Stress In the mentioning
confidence: 99%
“…41 The brain renin-angiotensin system is upregulated in chronic disease states such as hypertension and heart failure with enhanced central sympathetic outflow. [42][43][44][45][46][47] We also determined whether mitochondria-derived ROS mediates sympathoexcitation induced by angiotensin II in the RVLM. 19 It is well established that exogenously administered angiotensin II into the RVLM elicits the pressor response via the activation of the sympathetic nervous system.…”
Section: Sources Of Ros Production In the Rvlm In Hypertensionmentioning
confidence: 99%
“…It has been found that the angiotensin II type 1 receptors (AT 1 R) in the PVN are increased in SHR 11 and renovascular hypertensive rats. 12 Our recent studies have shown that angiotensin II (Ang II) in the PVN increases sympathetic activity and arterial pressure, and antagonist of AT 1 R in the PVN attenuates the enhanced sympathetic activity in renovascular hypertensive rats.…”
Section: Introductionmentioning
confidence: 99%